Determination of Aflatoxin and Pesticide Residues in Different Indian Chilli Varieties - Samreen Siddiqui, Dharini V, G. Sarath Chandra, S. Periyar Selvam, M. Mahesh Kumar (International Journal of Advanced Science and Technology, 2020)
Indian chilli (Capsicum annuum) varieties - Pusa jwala (Tamil Nadu), Pusa jwala (Uttar Pradesh), Byadgi (Karnataka), Guntur (Andhra Pradesh) and Kanthari (Kerala) were analysed for the determination of aflatoxin and pesticide residues. An attempt was made to determine the presence of aflatoxin in both fresh and dried samples of the selected varieties with thin layer chromatography (TLC) after the extraction process. The fresh chilli varieties were also analysed for the presence of residues of organochlorine (OC), organophosphorus (OP) and synthetic pyrethroid compounds (pesticides) using GC-MS/MS for compounds like deltamethrin, endosulfan, cypermethrin, etc. A total of 12 pesticides were evaluated in the samples. In the experiment, it was observed that there was absence of aflatoxin in fresh chilli samples. Even in the dried samples, which are widely used in India for making chilli powders, there was absence of aflatoxin in all tested varieties. No pesticide residues were found to be exceeding the prescribed maximum residue limits in any of the samples examined. Absence of pesticides may be related to the fact these compounds totally wear-off by the time chillies are harvested and commercialised. Thus, it can be concluded that these varieties are safe to consume if good agricultural practices (GAP) and good storage practices (GSP) are followed throughout the supply chain.